Dynamics of Dayah Ulama's Thoughts on Langsa City Qanun Regarding Entertainment Management - Faisal Faisal; Asmuni Asmuni; Phil. Zainul F (Jurnal Madania)
This study aims to discuss the dynamics of the understanding of dayah scholars towards Qanun Number 3 of 2016 concerning the Implementation of Entertainment in Langsa City. Qonun was born as a response to public anxiety about the phenomenon of mushrooming entertainment venues and sources of violence among the people of Langsa city. However, what is interesting is whether this qanun is accepted by all circles of society, especially by dayah or Acehnese ulama. This study is empirical juridical research. The data collection techniques used in this study were interview and documentation techniques. At the same time, the analysis technique used is descriptive. This research is located in Langsa city because the Islamization movement grows strong in public spaces and governance. The informants of this research came from dayah scholars, chairpersons or members of MPU Langsa city, as well as residents of Langsa city. An important finding in this study is that there have been differences in the views of dayah scholars on the qanun issued by the Langsa city government, especially Qanun Number 3 of Langsa City in 2016 regarding the implementation of entertainment in Langsa city, namely some approve and support, some do not support and do not need the qanun. The influence of dayah ulama on Qanun Number 3 of 2016 is very large and has support from the people of Langsa city, so what the dayah ulama says in the community is a fatwa or opinion that must be followed.